Increased Backward Wave Pressures Rather than Flow Explain Age-Dependent Heart Rate Effects on Central, But not Peripheral Arterial Pressure. Issue 2 (February 2022) - Mthembu, Nonhlanhla; Norton, Gavin R.; Peterson, Vernice R.; Naran, Ravi; Yusuf, Suraj M.; Tade, Grace; Bello, Hamza; Bamaiyi, Adamu; Libhaber, Carlos D.; Dessein, Patrick; Peters, Ferande; Sareli, Pinhas; et al.
Abstract : Through both backward (Pb) and forward (Pf) wave effects, a lower heart rate (HR) associates with increased central (PPc), beyond brachial pulse pressure (PP). However, the relative contribution to Pf of aortic flow (Q) versus re-reflection of Pb, has not been determined. Using central pressure, aortic velocity and diameter measurements in the outflow tract (echocardiography), we constructed central pressure waveforms that account for the relative contribution of Q versus re-reflection to Pf. We thus evaluated the mechanisms of HR-PPc relations in a community sample (n=824) and the impact of age thereon. Inverse HR-PPc ( P <0.0001), but not HR-brachial PP ( P =0.064) relations were noted. The slope of HR-PPc relation was increased in older adults ( P <0.005). HR was inversely associated with ventricular filling time, ejection duration, stroke volume, and peak Pf ( P <0.001 to P <0.0001). However, an increased Q and hence pressures generated by the product of aortic characteristic impedance and Q did not account for Pf effects. Age-dependent HR-PPc and Pf relations were both accounted for by enhanced Pb ( P <0.0001) with an increased Pf mediated by increments in wave re-reflection ( P <0.0001). The lack of impact of ejection duration on PPc was explained by an increased time to peak Pb ( P <0.0001). In conclusion, increases in PPc and Pf at a decreased HR are accounted for by an enhanced Pb rather than by a prolonged ejection or filling duration and hence flow (Q). These effects at a young-to-middle age are of little clinical significance, but at an older age, are of clinical importance. Abstract : Supplemental Digital Content is available in the text.